Pengaruh Tuntutan Pekerjaan, Modal Psikologis dan Kematangan Sosial terhadap Profesionalisme Karyawan - Arif Rachman Putra; Didit Darmawan; Mohammad Djaelani; Fayola Issalillah; Rafadi Khan Khayru (STIE Mandala Jember, 2022)
Human Resource Management is faced with the problem of being able to recruit employees who have the appropriate abilities for organizational goals and increase the desires of these employees. Management will prepare HR to achieve company goals starting from recruitment, selection, maintenance and development of each individual. This study aims to analyze and determine the effect of job demands, psychological capital and social maturity on employee professionalism and the most dominant factor among the three. this study used 142 respondents as a sample. the results obtained by multiple linear regression analysis. Based on the results of the study, several results were found which were stated as follows: job demands, psychological capital and social maturity had a partial significant effect on employee professionalism and job demands were the dominant variables on employee professionalism. Keywords: job demands, psychological capital, social maturity, employee professionalism.